♡ The Question ♡
・-2 (x + 7) = x -34 + 2x
*୨୧ ┈┈┈┈┈┈┈┈┈┈┈┈ ୨୧*
* ♡ The Answer ♡
・x = 4
*୨୧ ┈┈┈┈┈┈┈┈┈┈┈┈ ୨୧*
♡ The Explanation/Step-By-Step ♡
・-2 (x + 7) = x -34 + 2x
-2 (x + 7) = x + 2x - 34
-2 (x + 7) = 3x - 34
-2 (x + 7) : -2x - 14
-2 (x + 7)
Apply the distributive law! : a(b + c) = ab + ac
a = -2, b = x, c = 7
= -2 + (-2) x 7
Apply minus (-) plus rules!
+ (-a) = -a
= -2x - 2 x 7
Multiply the numbers! : 2 x 7 = 14
= -2x - 14
-2x - 14 = 3x - 34
Add 14 to both sides!
-2x - 14 + 14 = 3x - 34 + 14
Simplify!
-2x = 3x - 20
Subtract 3x from both sides!
-2x - 3x = 3x - 30 - 3x
Simplify!
-5x = -20
Divide both sides by -5!
-5x/-5 = -20/-5
Simplify! : -5x/-5 : x
Apply the fraction rule! : -a/-b = a/b
= 5x/5
Divide the numbers! : 5/5 = 1
= x
Simplify! : -20/-5 : 4
-20/-5
Apply the fraction rule! : -a/-b = a/b
= 20/5
Divide the numbers! 20/5 = 4
= 4
x = 4
*୨୧ ┈┈┈┈┈┈┈┈┈┈┈┈ ୨୧*
*♡ Tips ♡
・No tips provided!